PENGARUH STRATEGIC COSTING SEBAGAI STRATEGIC MANAGEMENT ACCOUNTING TECHNIQUES TERHADAP COMPETITIVE ADVANTAGE DAN ORGANIZATIONAL PERFORMANCE - Cynthia, Cynthia (Business Accounting Review, 2015)
The purpose of this study was to test the affect of Strategic Costing on Organizational Performance through Competitive Advantage that acted as the intervening variable on manufacturing companies in Surabaya and Sidoarjo. The sample of this study wasÂ  50 manufacturing companies in Surabaya and Sidoarjo. The data was collected by distributing questionnaires to the companies. This study used path modeling analysis technique with PLS tools. The results from this study showed that there were positive and significant affect of Strategic Costing on Competitive Advantage, positive and significant affect of Strategic Costing on Organizational Performance, and also positive and significant affect of Competitive Advantage on Organizational Performance on manufacturing companies in Surabaya and Sidoarjo.